Immunological Evidence of Variation in Exposure and Immune Response to Bacillus anthracis in Herbivores of Kruger and Etosha National Parks - Ochai, Sunday O.; Crafford, Jan E.; Hassim, Ayesha; Byaruhanga, Charles; Huang, Yen-Hua; Hartmann, Axel; Dekker, Edgar H.; van Schalkwyk, O. Louis; Kamath, Pauline L.; Turner, Wendy C.; van Heerden, Henriette (Frontiers in Immunology, 2022)
Exposure and immunity to generalist pathogens differ among host species and vary across spatial scales. Anthrax, caused by a multi-host bacterial pathogen, Bacillus anthracis, is enzootic in Kruger National Park (KNP), South Africa and Etosha National Park (ENP), Namibia. These parks share many of the same potential host species, yet the main anthrax host in one (greater kudu (Tragelaphus strepsiceros) in KNP and plains zebra (Equus quagga) in ENP) is only a minor host in the other. We investigated species and spatial patterns in anthrax mortalities, B. anthracis exposure, and the ability to neutralise the anthrax lethal toxin to determine if observed host mortality differences between locations could be attributed to population-level variation in pathogen exposure and/or immune response. Using serum collected from zebra and, kudu in high and low incidence areas of each park (target of 20 samples/species/area), we estimated pathogen exposure from anti-protective antigen (PA) antibody response using enzyme-linked immunosorbent assay (ELISA) and lethal toxin neutralisation with a toxin neutralisation assay (TNA). Serological evidence of pathogen exposure followed mortality patterns within each system (kudus: 95% positive in KNP versus 40% in ENP; zebras: 83% positive in ENP versus 63% in KNP). Animals in the high-incidence area of KNP had higher anti-PA responses than those in the low-incidence areas, but there were no significant differences in exposure by area within ENP. Toxin neutralizing ability was higher for host populations with lower exposure prevalence, i.e., higher in ENP kudus and KNP zebras than their conspecifics in the other park. These results indicate that host species differ in their exposure to and adaptive immunity against B. anthracis in the two parks. These patterns may be due to environmental differences such as vegetation, rainfall patterns, landscape or forage availability between these systems and their interplay with host behaviour (foraging or other risky behaviours), resulting in differences in exposure frequency and dose, and hence immune response.